Effect of Chicken Meatball Shelf Life With the Addition of Chitosan to Chemical Quality - Ikrima Rohimadilwa; Ludfia Windyasmara; Sri Sukaryani (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2021)
Chicken meatballs are one of the processed products that are very popular and favored by the public because they taste good and are nutritious. One way to preserve chicken meatballs is using borax or formalin which is bad for health. Chitosan is a natural preservative that comes from shrimp and crab waste that can be used in the long term. This study aims to determine the effect of adding chitosan as a natural preservative for chicken meatballs stored at room temperature on the quality of chicken meatballs which include moisture content, pH value and protein content. This research method used a completely randomized design with long storage factors and the addition of chitosan. The data obtained were analyzed statistically using Analysis of Variance (ANOVA). Further test with the Duncan Multiple Range Test (DMRT) if there is a significant difference between treatments. The variables recorded and observed were moisture content, pH value and protein content of chicken meatballs at room temperature (25ᴼC). The water content of chicken meatballs up to 1.5% chitosan addition treatment showed the best consistency during the shelf life with an average value of 59.31%. The pH value of chicken meatballs with the addition of 2.5% chitosan on the 2nd and 4th day gave a good effect with pH values of 5.56 and 5.78, respectively. Protein content of chicken meatballs with the addition of chitosan 1.5% on the second day gave the effect of increasing the highest protein content up to 7.21%. Keywords: Chicken meatballs, Chitosan, Shelf life